SUMBER DAYA LAUT INDONESIA DALAM KANCAH MASYARAKAT EKONOMI ASEAN, ANTARA JEBAKAN REIFIKASI DAN DEEP ECOLOGY - Rustamaji, Muhammad; Santoso, Bambang (Jurnal Media Hukum, 2014)
The  sea area of  Indonesia  reached 5.8 million  km2, with  a cluster of more  than 17,500  islands, promising a great  resource  in  facing  the ASEAN  single market. A  coastline  of  81,000  km which  is  actually  the  second longest  in  the world  after  Canada,  potentially,  become  a  storefront  variety  of  national  products which  are marketed around  the world.  But  the  single market  proposed  in  Asean  Economic Community  (AEC),  leaving homework, which  is  not  simple  in  the  ecological  sector.  The purpose  of  this writing  is  actually wanting  to show challenges  that must be faced when AEC creating  a single ASEAN market. Based on  the categorization of  legal  study analysis method,  the method  in use,  including method of dogmatic  research which developed legal  studies  as  a dogmatic  law  (Rechtsdogmatiek).  The  results  showed  that,  consciously or  not,  the Asean single market has brought a new myth called rationality efficiency of the commodity. Horkheimer and Adorno in  their  enlightment  dialectic  explained  that  in  the  field  of  economy,  efficiency  is  the  law  of  the market, substitutes  all  kinds of  feudal  and  religious  restrictions.  Then  rationality  equated with  efficiency. When  this efficiency is applied in the dynamics of the capitalist economy, what happens next is the entire field of human life will  become  a  commodity.  Then  came  the  so-called  reification,  that  is when  everything  becomes  acommodity,  people  no  longer  feel  enjoy  but  only  for  the  sake  of  consumption without  establishing  social relations  in  the  true  sense. At  this  situation,  the  ecological  damage  becomes  inevitable,  even  consideredreasonable  as  a price worth paying.  Law, which  in  essence  is  the  ethical  conversation  humans  to  produce justice,  easily  forgotten  because  of  greed.  In-depth  perspective  on  the  ecological  (deep  ecology), which essentially  is  in  the  interests  of  civilization,  began  excluded. But  all  such  reification  excesses  can  be  avoided when the law still pursued progressively, so the law must arrive at the radicality demolition on law assumptions. The  law  is not only  to  check  the  fairness,  but  it  should produce  justice, even  a new  kind of  justice,  namely justice  for the sake of  future generations  (intergeneration  justice).  It can be concluded  that the ocean  should not only being  taken  for  its wealth  resources  in  the  trap of  reification of  the ASEAN  single market, but also should be maintained,  its preservation  for  the  sake of our next generation  in  regard of  deep ecology.